Exploring the use of ICT by language instructors at a university in Kazakhstan: Expectations, realities, and factors influencing adoption - Nogaibayeva, Akmarzhan (Teaching English as a Foreign Language Journal, 2023)
The field of English Language Teaching (ELT) is undergoing a revolutionary shift in response to the spread of English as a lingua franca around the world, aligning itself with the needs of English as a tool for international communication (Cameron & Galloway, 2019). This change calls for a closer look at how teachers use information and communication technology (ICT) in ELT and how they view the changing environment. Research on educators’ attitudes about the use of ICT is crucial to examine before adopting such changes to ICT use practices, since this offers invaluable insights into the viability of curriculum innovation in language teaching and learning. There have been more studies addressing language attitudes on ICT use, but there remains a scarcity of studies that look at instructors’ views regarding ICT use beliefs from the perspective of multilingualism. Even though the body of knowledge about language instructors’ attitudes has grown, few studies have looked at teachers’ attitudes about ICT use from the perspective of their multilingualism (Dalvit, 2010). By filling this important gap, the current study aims to clarify how instructors’ perceptions of English, Russian and Kazakh in Kazakhstan’s higher education context interact with micro (personal beliefs), meso (colleagues in the department) and macro (wider environment). These attitudes have the potential to have a substantial impact on how successfully ICT use approaches are incorporated into a multilingual educational environment. Our understanding of how teachers’ ICT use attitudes manifest within the Kazakh multilingual context.